The effect of welding current on mechanical properties of Galvanized steel sheets in resistance spot welding (RSW) - Muhammad Rifki Ismail (Universiti Malaysia Perlis, 2008)
This study about the effect of welding current and the cycles on the quality of weld joint on galvanized steel sheets using resistance spot welding. Examinations involve tensile shear and tensile peel strength (T-peel test) of the galvanized steel sheet that have about 3.0mm in thickness. The goal of this research is to examine the behavior of the spot welding on the galvanized steel sheet to avoid the corrosion problem in automobile industries. Welding periods refer to the cycles or the time that how long current will flow through the metal sheet. If the metal galvanized with the different type of element it will change the values of current flow or the resistances readings. Spot welder machine that provided at the UniMAP MC 15 from welding industries (Malaysia) Sdn. Bhd. and have highest cycles 10 cycles and for the current 6 kA. This type of spot welding machine has electronic timer and mechanical forced. The joints was spot welded using 3 kA, 5 kA and 6 kA and cycle 4, 6, and 8. Force also one of the important parameters in spot welding mechanism, but for this examination, the force was kept constantly about 150 KGF. After the sample preparation have done, the specimens are ready to exposed to the tensile shear and tensile peel (T-peel) test using universal testing machine (UTM). Average, the result for the study indicate that tensile shear strength are lower than tensile peel strength respectively.